Frozen II. Spirits of nature - Bouchard, Natasha; Disney Storybook Artists (New York : Random House, 2019)
Elsa meets the spirits of nature who live in the Enchanted Forest.
Based on: Frozen II.
2.0.
K-3.
410L
Keywords: Queens -- Juvenile fiction; Sisters -- Juvenile fiction; Magic -- Juvenile fiction; Kings, queens, rulers, etc. -- Fiction; Sisters -- Fiction; Magic -- Fiction; Fantasy; Fantasy fiction; Adaptations; Readers (Elementary)